Epidemiological trends of HBV and HDV coinfection among Viennese HIV+ patients. (5th August 2021) - Schmidbauer, Caroline; Chromy, David; Schmidbauer, Victor U.; Schwarz, Michael; Jachs, Mathias; Bauer, David J. M.; Binter, Teresa; Apata, Michael; Nguyen, Dung T.; Mandorfer, Mattias; Simbrunner, Benedikt; Rieger, Armin; et al.
Abstract: Background and Aims: Despite vaccination recommendations, hepatitis B (HBV) and D (HDV) coinfections are common in HIV+individuals. Methods: HBV immunization status (anti‐HBs) as well as HBV (HBsAg/HBV‐DNA) and HDV (anti‐HDV) coinfection rates were assessed in 1870 HIV+individuals at HIV diagnosis (baseline, BL) and last follow‐up (FU). Results: Sixty‐eight (3.6%) HIV patients were never tested for HBV. At BL, 89/1802 (4.9%) HIV patients were HBV coinfected. Four hundred and fifteen (23.0%) showed virological HBV clearance [HBsAg(‐)/anti‐HBc(+)/anti‐HBs(+)] and 210 (11.7%) presented with anti‐HBc(+) only. Seven hundred and ten (39.4%) were HBV naïve [HBsAg(‐)/anti‐HBs(‐)/anti‐HBc(‐)/HBV‐DNA(‐)], but only 378 (21.0%) received vaccinations with detectable anti‐HBs(+) titres. Among the 89 HBV/HIV‐coinfected patients, only 52 (58.4%) were tested for HDV: 11/49 (22.4%) had anti‐HDV(+) and 3/12 (25.0%) showed HDV‐RNA viraemia. During a median FU of 6.5 (IQR 7.2) years, 44 (4.6%) of the 953 retested BL HBV‐negative patients acquired new HBV infection (including 15/304, 4.9% of vaccinated patients). Of the 89 patients, 22 (24.7%) patients cleared their HBsAg, resulting in 60/1625 (3.7%) HIV/HBV individuals at FU: 34 (56.7%) showed HBV‐DNA suppression and 15 (25.0%) were HBV viraemic, while 12/89 (13.5%) remained without a FU test. Vaccinations induced anti‐HBs(+) in 137 of the retested 649 (21.1%) BL HBV‐naïve patients. Conclusion: HBV testing is well established among Viennese HIV+patients with HBV coinfection rates around 4%‐5%. HBV vaccinations are insufficiently implemented since anti‐HBs titres were detected in only 21.1% of HBV‐naive HIV(+) patients and new HBV infections occurred in previously vaccinated patients. HDV testing is not systematically performed despite up to 25% of HIV/HBV patients may show HDV coinfection.